Piloting The CARD™ System for education of students about vaccination: Does it improve the vaccination experience at school?. (29th March 2019) - Taddio, Anna; Ilersich, Anthony N T; Ilersich, Angelo L T; Schmidt, Cathryn; Chalmers, Garth; Wilson, Evelyn; McMurtry, C Meghan; MacDonald, Noni; Bucci, Lucie M; Freedman, Tamlyn; Wong, Horace
Abstract: Objective: Many students are fearful of vaccine injection-associated pain. In prior research, we created Knowledge Translation (KT) tools to address school vaccinations and associated pain, fear, and fainting. The objectives of this pilot implementation project were to determine the acceptability and impact of these KT tools on student knowledge, attitudes, and perceptions of their vaccination experience. Methods: Pre–post mixed methods design. Students in an independent school in the Greater Toronto Area, Ontario, participated in two separate focus groups before and after school vaccinations. In both sessions, they independently completed a knowledge and attitudes survey, reviewed three KT tools (two videos and one pamphlet) and then repeated the knowledge and attitudes survey. They provided structured and qualitative feedback about the KT tools and described the impact of the education on the vaccination experience. Results: Altogether, 11 grade 7 students participated. Knowledge scores were higher post-tool review compared to baseline in the first focus group. There was no significant difference in fear scores and attitudes about getting vaccinated. Qualitative feedback was categorized into two themes: intervention characteristics and characteristics of the school environment. Students reported the KT tools helped them to prepare for vaccination. They used the information on vaccination day to reduce their own fear and pain and to assist peers. They believed all students should view the KT tools. Students reported that teachers and nurses did not do enough to make vaccinations a positive experience. For example, they did not provide a private setting as an option for vaccination and prevented them from using some coping strategies recommended in the KT tools. Discussion: This study provides preliminary evidence of the acceptability and positive impact of the KT tools on students' vaccination experiences. Future research is recommended that involves inclusion of all students and adults in the KT intervention.